Potential Climate Change Adaptation Strategies Suitable in the Philippine Setting - Ericson E. Coracero (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Climate change is one of the most challenging environmental issues being faced by the world. Its effects are slowly getting worse and unbearable. Adaptation techniques are important to learn how to deal and live with climate change, and somehow address it. This paper provides possible practices and ways of adaptation to climate change that can be of help to the people. These ways include three major components: use of technical practices and strategies, execution of site-based programs, and raising people’s awareness and sense of responsibility. These practices can help address the problem and improve the way of living of people while also improving the environment’s situation.